Larval trematodes from Biomphalaria straminea (Mollusca, Planorbidae) in a ricefield in Corrientes Province, Argentina. - Fernández, María Virginia (2013)
A total of 3 494 snails from Biomphalaria straminea (Dunker, 1848) were collected from December 2010 to May 2011, in a ricefield in Corrientes province, Argentina, and 5 species of larval trematodes belonging to Strigeidae (Furcocercaria sp. XIV, Furcocercaria sp. XV, Furcocercaria sp. XVI), Diplostomidae (Furcocercaria sp. XVII) and Schistosomatidae (Furcocercaria sp. XVIII) found in 115 snails (3.29%) are described. Prevalence of infection ranged between 0.11% (e.g., Furcocercaria sp. XVIII) and 4.22% (e.g., Furcocercaria sp. XVI) in the snails examined. Furcocercaria sp. XIV, Furcocercaria sp. XV and Furcocercaria sp. XVI were the most common species present in nearly all months of the sampling period, whereas Furcocercaria sp. XVII and Furcocercaria sp. XVIII were rarer species. Infection rates of most larval digeneans were highest in March. The species of furcocercariae in B. straminea from the agricultural habitat described in the present study are now added to the 4 species of furcocercariae already reported for the region from the genus Biomphalaria.